Mother-in-Law–Daughter-in-Law Relationship in the Current Korean Society - Elena Buja (Acta Universitatis Sapientiae: Philologica)
One of the prevailing themes in Korean novels and dramas is the fractured relationship between mothers-in-law and daughters-in-law, caused to a great extent by Confucianism, which preaches submissiveness of women to their parents, husbands, and in-laws. Given the tremendous economic, technological, and cultural development of South Korea in the last fifty years, the question that arises is whether family ties have undergone an equal progress. This study aims at identifying whether the matriarch in the Korean household, i.e. the mother-in-law, still holds the reins or whether there is a shift towards more freedom and independence of the daughtersin-law. The data employed to this aim are Cho Nam-Joo’s (2018) novel Kim Jiyoung, Born 1982, which follows the life of a married woman in her thirties and a K-drama titled Marriage Clinic: Love and War that depicts the problems of married couples, among which the bad treatment daughters-inlaw receive from their husbands’ mothers. The theoretical framework for the analysis is a combination of critical discourse analysis (Wodak & Mayer 2001, Fairclough 2010), which is employed for “investigating language in relation to power and ideology” (Wodak 2001: 2) and Foucault’s (1983) theory related to power and the subject. The findings indicate various manners in which Korean mothers-in-law in twenty-first-century South Korea exercise power over their daughters-in-law and also ingenious ways in which the latter manage to counteract this dominance.